Dependence of blood T2 on oxygenation at 7 T: In vitro calibration and in vivo application. Issue 6 (10th July 2013) - Krishnamurthy, Lisa C.; Liu, Peiying; Xu, Feng; Uh, Jinsoo; Dimitrov, Ivan; Lu, Hanzhang
<x xml:space="preserve">Abstract</x> Purpose The calibratable relationship between blood oxygenation (Y) and T2 allows quantification of cerebral venous oxygenation. We aim to establish a calibration plot between blood T2, Y, and hematocrit at 7 T, and using T2‐relaxation‐under‐spin‐tagging MRI, determine human venous blood oxygenation in vivo. Methods In vitro experiments were performed at 7 T on bovine blood samples using a Carr‐Purcell‐Meiboom‐Gill‐T2 sequence, from which we characterized the relationship among T2, Y, and hematocrit. T2‐relaxation‐under‐spin‐tagging MRI was implemented at 7 T to measure venous blood T2 in vivo, from which oxygenation was estimated using the in vitro calibration plot. Hyperoxia was performed to test the sensitivity of the method to oxygenation changes, and the 7 T results were compared with those at 3 T. Results In vitro data showed that arterial and venous T2 at 7 T are 68 and 20 ms, respectively, at a typical hematocrit of 0.42. In vivo measurement showed a cerebral venous oxygenation of 64.7 ± 5.0% and a test‐retest coefficient‐of‐variation of 3.6 ± 2.4%. Hyperoxia increased Yv by 9.0 ± 1.4% (P = 0.001) and the 3 and 7 T results showed a strong correlation (R = 0.95) across individuals. Conclusion We provided an in vitro calibration plot for conversion of blood T2 to oxygenation at 7 T and demonstrated its utility in vivo. Magn Reson Med 71:2035–2042, 2014. © 2013 Wiley Periodicals, Inc.